2021
DOI: 10.3390/cancers13164006
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Theory of Cancer: Origin of Tumor Heterogeneity and Plasticity

Abstract: In many respects, heterogeneity is one of the most striking revelations and common manifestations of a stem cell origin of cancer. We observe heterogeneity in myriad mixed tumors including testicular, lung, and breast cancers. We recognize heterogeneity in diverse tumor subtypes in prostate and kidney cancers. From this perspective, we illustrate that one of the main stem-ness characteristics, i.e., the ability to differentiate into diverse and multiple lineages, is central to tumor heterogeneity. We postulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 51 publications
3
18
0
Order By: Relevance
“…Thus, we referred to C1 as "low stemness subtype" and C2 as "high stemness subtype". Further prognostic and clinical analysis revealed that C2 possessed dismal prognosis and more advanced tumors, which were in line with the properties of high stemness tumors (5,19).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Thus, we referred to C1 as "low stemness subtype" and C2 as "high stemness subtype". Further prognostic and clinical analysis revealed that C2 possessed dismal prognosis and more advanced tumors, which were in line with the properties of high stemness tumors (5,19).…”
Section: Discussionmentioning
confidence: 53%
“…Mounting evidence have established the links between cancer stemness and intratumoral heterogeneity across cancer (2,9,10,18), and a theory believes cancer stemness is the origin of intratumoral heterogeneity and plasticity (19). Currently, the intertumoral heterogeneity of cancer stemness remains elusive in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, low ITH high SCNAs reflect aneuploidy and implicate aberrant asymmetric division, suggesting that a stemness origin may be involved in the evolution of this malignant phenotype [29]. In principle, when we have treatments that keep a primary tumor or its metastatic lesions stable or dormant, surgery may be beneficial even in the setting of metastatic disease.…”
Section: Primary Vs Metastatic Cancermentioning
confidence: 99%
“…Problem is that recent evidence indicates that most cancerous prostates harbor genetically distinct, independently developing malign clones [10]. This tumor heterogeneity [11,12], both at histo-pathological and transcriptomic [13,14] levels within the prostate of one patient as well as among patients, complicates significantly the treatment options [15][16][17]. Moreover, together with the biomarker(s) whose altered sequence or expression level is thought indicative for that cancer type, unique combinations of hundreds other genes are mutated or/and regulated in each cancer nodule with respect to the surrounding, cancer-free tissue [18].…”
Section: Introductionmentioning
confidence: 99%
“…This explains the observed wide diversity of PCa forms and the large spectrum of treatment outcomes. Therefore, it is imperious to go beyond precision medicine [12,19] to treatments tailored to the unrepeatable characteristics of every single patient at each moment of his life.…”
Section: Introductionmentioning
confidence: 99%